A Review on the Effect of Cell Phone Electromagnetic Radiation on Histological Testicles - Farmananda, Irsandi Rizki; Farindra, Irmawan; Linawati, Ni Made (Universitas Malahayati, 2024)
ABSTRACT Cell phones have become an essential possession for individuals in today's society. Nevertheless, beneath their widespread use lies a potential hazard in the form of electromagnetic radiation. The level of radiation emitted varies, along with its impact on the human body, particularly on the reproductive system. This research aims to consolidate findings from existing studies on the influence of cell phone electromagnetic radiation on the histological makeup of the testes. A review of literature was conducted following a PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) approach, utilizing the PubMed and Scopus journal publication databases. A total of 133 articles were identified through the database search, with inclusion and exclusion criteria established based on the PICOS framework. Following the screening process, six articles met the predetermined criteria and were deemed suitable for analysis. The results of the study demonstrate that exposure to electromagnetic radiation led to alterations in the histological structure of the testes in experimental animals. In conclusion, prolonged exposure to electromagnetic radiation has an impact on the histological composition of the testes in experimental animals. Keywords: Electromagnetic Radiation, Histology, Testicles, Cell Phone